Role of Small Intestinal Bacterial Overgrowth (SIBO) and Inflammation in Obese Children - Esposito, Susanna; Biscarini, Anna; Federici, Barbara; Cofini, Marta; Argentiero, Alberto; Neglia, Cosimo; Lanciotti, Lucia; de' Angelis, Gian Luigi; Principi, Nicola (Frontiers in Pediatrics, 2020)
Knowledge of the real incidence of small intestinal bacterial overgrowth (SIBO) in obese children and its role in obesity development seems essential for a more effective approach to the treatment of this condition. In this prospective, single-blind study, presence of SIBO was evaluated in a group of children with overweight/obesity. A blood sample for evaluation of cytokine profile was collected to establish the potential relationship with inflammatory condition and lactulose breath test (LBT) to diagnose SIBO was performed. A total of 36 patients with excess of adipose tissue were recruited. Among them, 16 (44.4%) were overweight and 20 (45.6%) were obese. Overall, 26 (72.2%) children had a positive LBT and were considered suffering from SIBO, 12 (75.0%) among those overweight and 14 (70.0%) among those obese. Measurement of cytokines (IL-1α, IL-1β, IL-4, IL-6, IL-7, IL-8, IL-10, IL-12p40, IL-12p70, IL-17, IFN-α2, IFN-γ, TNF-α), cytokine antagonists (IL-1ra), chemokines (IP10, MCP-1, MIP1α, MIP1β), and growth factors (EGF, G-CSF, GM-CSF, and VEGF) secreted in culture supernatants by PHA activated-PBMCs revealed that in the study population proinflammatory cytokines IL-1, IL-6, IL-8, IL-12, IFN-γ, IL-18, and TNF-α were high, whereas anti-inflammatory mediators IL-4 and IL-10 were low. However, no significance difference between children with SIBO and those without were evidenced. Evaluation of relationship of severity of SIBO showed a significant positive relationship between EGF or IFN-α2 and H2 but not CH4 levels and an inverse significant relationship with CH4 but not H2. Although further studies are needed to confirm our results, this study highlights that SIBO is extremely common in overweight and obese children and can be demonstrated not only in severely obese subjects but also in moderately overweight patients. The inflammatory state seems to precede obesity development and SIBO does not seem to have relevance in obesity development, with no relationship found between severity of SIBO and inflammatory state.